3Cat-8 Mission: A 6-Unit CubeSat for Ionospheric Multisensing and Technology Demonstration Test-Bed - Luis Contreras-Benito; Ksenia Osipova; Jeimmy Nataly Buitrago-Leiva; Guillem Gracia-Sola; Francesco Coppa; Pau Climent-Salazar; Paula Sopena-Coello; Diego Garcín; Juan Ramos-Castro; Adriano Camps (Remote Sensing, 2024)
This paper presents the mission analysis of 3Cat-8, a 6-Unit CubeSat mission being developed by the UPC NanoSat Lab for ionospheric research. The primary objective of the mission is to monitor the ionospheric scintillation of the aurora, and to perform several technological demonstrations. The satellite incorporates several novel systems, including a deployable Fresnel Zone Plate Antenna (FZPA), an integrated PocketQube deployer, a dual-receiver GNSS board for radio occultation and reflectometry experiments, and a polarimetric multi-spectral imager for auroral emission observations. The mission design, the suite of payloads, and the concept of operations are described in detail. This paper discusses the current development status of 3Cat-8, with several subsystems already developed and others in the final design phase. It is expected that the data gathered by 3Cat-8 will contribute to a better understanding of ionospheric effects on radio wave propagation and demonstrate the feasibility of compact remote sensors in a CubeSat platform.